In-Sillico Evaluation of Asystasiagangetica Phytoconstituents against Multiple Molecular Targets associated with Cystic Bronchitis (International Journal of Research in Pharmaceutical Sciences and Technology, 2026)
Cystic bronchitis is a chronic inflammatory airway condition characterized by bronchial inflammation and the formation of cyst-like sacs, leading to decline in lung function and Current management strategies for cystic bronchitis provide immediate relief but primarily focus on symptom control rather than disease modification and long-term management. These gaps highlight the need for multifunctional therapeutic strategies that can simultaneously address inflammation, oxidative stress, mucus dysregulation, and disease progression in cystic bronchitis Objective: This study aimed to identify key therapeutic targets responsible for the accumulation of dehydrated, acidic, and viscous mucus, and to discover potential lead compounds from the phytochemical profile of Asystasiagangetica by using ML pipeline tools. Methodology: We identified a multi-target network involved in this pathology, including Nuclear factor kappa B, Cyclooxygenase-2, Tumor necrosis factor-alpha, Interleukin-6, Inducible nitric oxide synthase, Kelch-like ECH-associated protein 1, Toll-like receptor 4, and Mucin 5AC. For lead identification, a total of 235 compounds identified via GC-MS were screened using a Machine Learning (ML) pipeline. Compounds were filtered based on Lipinski’s Rule of Five, Veber’s Bioavailability parameters, and Egan’s Absorption criteria, resulting in 15 high-priority phytoconstituents for molecular docking. Result: Among these, Lupeol exhibited significant inhibitory potential across all identified targets. These findings suggest that Lupeol is a promising candidate for treating cystic bronchitis. Conclusion: cystic bronchitis is a chronic inflammatory condition which lead to the accumulation of mucus and bacterial colonization in the lung resulting in decline lung function. Multi-Target approach that target the inflammation will provide a much better and long term relief. This study show that the Lupeolhas a potential multi-target inhibitors. Though further in-vitro assays, molecular dynamics (MD) simulations, and in-vivo studies are required for validation.
Keywords: Cystic Bronchitis; Asystasiagangetica; Lead Identification; ML Pipeline; Lupeol; Molecular Docking; MUC5AC